2021
DOI: 10.1021/acs.jnatprod.0c01018
|View full text |Cite
|
Sign up to set email alerts
|

Natural Piperine Improves Lipid Metabolic Profile of High-Fat Diet-Fed Mice by Upregulating SR-B1 and ABCG8 Transporters

Abstract: Natural piperine from black pepper is known to function as hypocholesterolemic agent, but how it lowers the blood cholesterol remains unclear. In this study, we found that intragastric administrations of piperine (25 mg/kg/day) for 8 weeks significantly reduced the plasma triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) in high-fat diet (HFD)-fed mice. H&E staining indicated that piperine significantly decreased hepatic lipid accumulation compared with the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…As presented in Figure 4 C–F, OA elevated cellular TG, TC, and LDL-C contents and reduced the level of HDL-C compared to the control group, suggesting that OA disrupted the lipid metabolism homeostasis in HepG2 cells. It was reported that PIP could regulate lipid levels by enhancing cholesterol efflux, reducing cholesterol uptake, and leading to a reversal of hepatic homeostasis induced by HFD [ 24 ]. In our experiment, after PIP treatment, TG, TC, and LDL-C contents were reduced dose-dependent, showing that PIP ameliorated the accumulation of lipids in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 4 C–F, OA elevated cellular TG, TC, and LDL-C contents and reduced the level of HDL-C compared to the control group, suggesting that OA disrupted the lipid metabolism homeostasis in HepG2 cells. It was reported that PIP could regulate lipid levels by enhancing cholesterol efflux, reducing cholesterol uptake, and leading to a reversal of hepatic homeostasis induced by HFD [ 24 ]. In our experiment, after PIP treatment, TG, TC, and LDL-C contents were reduced dose-dependent, showing that PIP ameliorated the accumulation of lipids in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…cubense , Cucumber fusarium wilt , Cowpea wilt , F. graminearum , Nectria sp., F. mangiferae , C. asianum, and Alternaria solani ., using a disk diffusion and half dilution method ( Zhang et al, 2019 ). Effect of know compounds 6 , 7 , 8 , 11 , and 12 on serum-mediated cholesterol efflux and on cell viability in J774A.1 macrophages were also tested ( Sankaranarayanan et al, 2011 ; Wang et al, 2017 ; Hou et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Establishment of the Hyperlipidemic Model and Evodiamine Treatment. Mice were fed with a normal diet or a high-fat diet following the recipes 24 consisting of 3% cholesterol, 10% lard, 0.5% bile salt (pig) (Table 2). After 3 weeks of HFD, mouse blood was collected from the tail vein and plasma lipid levels were determined for verifying the establishment of a hyperlipidemic model.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…After embedding in histoplast paraffin, the liver tissues were cut into 5 μm sections using a coolclamp tissue microtome (Leica, RM2255, Germany). Then the above sections were stained using modified H&E. 24 Images of sections were captured by a microscope (Nikon, Eclipse TS100, Japan).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation